2016
DOI: 10.2217/cnc-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic brain injury and mental health problems among individuals within the criminal justice system

Abstract: Traumatic brain injury (TBI) is associated with increased aggression and antisocial behavior. This review examined existing literature regarding TBI prevalence and associated adverse mental health among individuals within the criminal justice system. TBI prevalence varied between 12 and 82% for youths, and 23 and 87% for adults. TBI was associated with a range of negative outcomes, particularly substance abuse. However, confounding factors, including differing control groups, lack of information for timing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…A growing body of work has developed around traumatic brain injury (TBI) within offender populations, with past meta-analyses consistently reporting high levels of TBI in both adult (1) and juvenile offenders (2). With the focus of such work primarily on male offenders, there is a dearth of available research surrounding female offenders with TBI (3)(4)(5)(6). Of the nine prevalence studies identified (7)(8)(9)(10)(11)(12)(13)(14)(15) rates of TBI differed considerably, from 22.7% (11) to 100% (8).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of work has developed around traumatic brain injury (TBI) within offender populations, with past meta-analyses consistently reporting high levels of TBI in both adult (1) and juvenile offenders (2). With the focus of such work primarily on male offenders, there is a dearth of available research surrounding female offenders with TBI (3)(4)(5)(6). Of the nine prevalence studies identified (7)(8)(9)(10)(11)(12)(13)(14)(15) rates of TBI differed considerably, from 22.7% (11) to 100% (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 48% to 82% of individuals in the prison system have a history of TBI. [ 30 ] One of the factor that can be assessed in subsequent studies may be the emotional experience related to possible trauma suffered in childhood and beyond, which may have influenced cognitive degeneration causing deviant personality traits related to crime. Measures of children's adversity (e.g., physical abuse, physical abandonment, sexual abuse, emotional abuse, emotional abandonment) could be assessed through the childhood trauma questionnaire [ 31 ] which demonstrated internal consistency, convergent and discriminating validity, good sensitivity and satisfactory levels of specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of selfreport in both TBI screening and outcome measurement is not ideal and may have adversely impacted results. Self-report of TBI is prone to both under-reporting and false recall of incidents particularly for injuries at younger ages (25), however, research suggests offender self-report of TBI is generally accurate (62). Participants in the control group were older and more highly educated that those in the offender group.…”
Section: Limitationsmentioning
confidence: 95%
“…Within the custodial estate, offenders with TBI have been shown to have higher rates of infractions than offenders without TBI which have been attributed to higher levels of aggression (22). Prisoners with TBI are at a significantly heightened risk of mental illness (23)(24)(25) with increased aggression and behavioural problems serving to increase their isolation and vulnerability. The removal of liberty and contact with loved ones leads to reduced social support and increased isolation, which is a contributory factor towards poor mental health (26).…”
Section: Introductionmentioning
confidence: 99%